The Correlation between Emotional Maturity and Career Decision Making among Twelfth Grade Students - Yulianti, Dwi Indah; Nurhayani, Nurhayani (Buletin Konseling Inovatif, 2025)
Indicators of emotional maturity that can influence career decision-making among 12th-grade students include stress management ability, the ability to delay gratification, self-control, and emotional stability. The higher students' score on these indicators indicates their greater opportunity to make appropriate career decisions. The aim of this study is to determine the relationship between emotional maturity and career decision-making among 12th-grade students at State Senior High School 1 Pulau Rakyat Tua. This research employed a descriptive method with a quantitative approach. The findings of this study indicate a correlation between emotional maturity and career decision-making in 12th-grade students at State Senior High School 1 Pulau Rakyat Tua. This relationship is positive, as evidenced by a Pearson correlation value of 0.365. The relationship between these two variables, as indicated by the Pearson correlation, is weak, given that the value does not exceed 0.40 or 0.365 < r. The absolute value of r is between 0.25 and 0.50. Career decision-making maturity in students contributes to a better understanding of themselves, such as recognizing their interests, talents, and weaknesses. It also involves exploring career opportunities that match their potential, including information about continuing education or employment.